Design like you give a damn architectural responses to humanitarian crises - Architecture for Humanity (Organization). (London Thames & Hudson, 2006)
" Edited by architecture for Humanity, a volunteer-based organization that provides architectural solutions to humanitarian crises, Design Like You Give a damm brings the best of humanitarian design to the printed page. Proceeds from the sale of this book will support the work of Architecture for Humanity."
I hope it?s a long list /Cameron Sinclair -- 100 years of humanitarian design /Kate Stohr -- Lightweight emergency tent /Office of the United Nations High Commissioner for Refugees -- Shelter frame kit /World Shelters ;interview /Bruce LeBel -- GripClips /Shelter Systems -- BOLD /CHF International -- Global Village Shelters /Ferrara Design -- Burning Man Shelter tests : Podville /Icosa Village ; Hexayurt /Vinay Gupta -- Unofficial Strong Angel training exercises /Strong Angel -- Concrete canvas /Peter Brewis, William Crawford -- 139 Shelter /Future Systems -- Transitional Community /Oxfam -- Paper church ; Paper log houses ; Paper tube emergency shelter /Shigeru Ban Architects -- Super adobe /Cal-Earth ; interview, Nader Khalili -- Pallet house /I-Beam Design -- Rubble house /LA Architects -- Low-tech balloon system /TechnoCraft -- Extreme housing / Deborah Gans, Matt Jelacic -- Prefabricated core housing ; Core housing /Relief International -- Safe(R) House / Harvard, MIT -- Housing in northern Afghanistan /Shelter for Life -- Mobile migrant worker housing ; Pink houses with greenhouses / Design Corps -- Maasai Integrated Shelter Project / Intermediate Technology Development Group -- Lucy House ; 20.0 House / Rural Studio -- Hopi Nation Elder Home /Red Feather Development Group -- Bayview Rural Village /RBGC Architecture, Research & Urbanism ; interview, Maurice D. Cox -- Quinta Monroy Housing Project / Elemental Housing Initiative, Taller de Chile -- Northern Ireland Cross-Community Initiative /Habitat for Humanity, Northern Ireland -- Sistema Arde /Hierve-Diseñeria -- Huts and low-riders /Mad Housers -- Dome Village /Justiceville, USA -- First Step Housing /Common Ground Community -- Parasite /Michael Rakowitz -- Mason?s Bend Chapel /Rural Studio -- Appirampattu Village Center /Logan Allen -- Barefoot College /Barefoot Architects -- Homeboy Industries / Detroit Collaborative Design Center -- Center for Disabled Workers / Technical University, Vienna -- Siyathemba Soccer "clinic" /Swee Hong Ng -- Favela-Bairro Projects / Jorge Mario Jáuregui Architects -- Rufisque Women?s Centre /Hollmẽn Reuter Sandman Architects -- Shelter 2 / Christopher Livingston, Montana State University -- Mobile health clinic /atelier [gilliland tolila] -- Africa Centre for Health and Population Studies /East Coast Architects -- Medwed Clinic /Michal Vital, Yuval Amir -- Gando Primary School /Diébédo Francis Kéré -- Bamboo Primary School /theskyisbeautiful architecture -- Druk White Lotus School /Arup Associates -- School solar kitchen /BASIC Initiative, College of Architecture and Urban Planning, University of Washington -- Hole-in-the-Wall Schools /Dr. Sugata Mitra -- A bridge too far /Chinese University of Hong Kong -- Hippo Water Roller /Grant Gibbs -- PlayPump /Roundabout Outdoor ; interview, Trevor Field -- Ceramic water filter / Potters for Peace -- Watercone / Stephan Augustin -- MoneyMaker Pumps / KickStart -- Long-lasting antimalaria bed nets / Acumen Fund, Sumitomo Chemical Corp. -- Aquacube / Süd-Chemie -- Clean Hub System / Shelter Architecture -- Power Shade / FTL Design Engineering Studio -- Seba Dalkai School solar classroom / Native American Photovoltaics -- Himalayan Rescue Association Pheriche Clinic / Lotus Energy -- VIP latrine / Arup Associates -- Living Machine /Basic Initiative, College of Architecture and Urban Planning, University of Washington -- Ecological dry toilet /Cësar Añorve -- UnBathroom /William Hsu -- shelterproject / shelterproject.org -- Sphere Project /Steering Committee for Humanitarian Response, InterAction -- Roots of Peace /Heidi Kühn, Gary Kühn, Kyleigh Kühn -- European Greenbelt /World Conservation Union -- A civilian occupation : the politics of Israeli architecture /Rafi Segal, Eyal Weizman -- Sleeping Bag Project /Project Locus -- Housing for health / Paul Pholeros, Stephan Rainow, Paul Torzillo -- Viewing platforms ; Stair to park / Heavy Trash -- Finding public space in the margins /Center for Community Research and Design, Woodbury University -- City without a ghetto / Center for Urban Pedagogy -- Shrinking Cities / Shrinking Cities -- Urban acupuncture /Curitiba, Brazil.
Keywords: Architecture and society; Emergency housing -- Design and construction; Disaster victims -- Dwellings; Buildings, Temporary -- Designs and construction; Sustainable architecture